Carbon dioxide in biomass processing: contributions to the green biorefinery concept - Morais, Ana Rita C. (2016)
The 21st century is witnessing a huge demand of fossil reserves coupled with a rapid reduction in readily and economically reachable oil feedstocks.The present energy demand is not fulfilled from fossil fuel sources, making the world exposed to geopolitical risk. Furthermore, concerns regarding the security of the supply chain and the environmental impacts have resulted in an ever-increasing shift of global energy policies to seek alternative technologies and sustainable sources of energy, materials, chemicals, and value-added products. Recently, the need for development of an economy based on renewable resources has been recognized by society, and diverse R&D activities have started to be funded to accomplish this aim. However, generation of bioproducts based on sustainable supply chains poses vast challenges for an eco-based economy.The simplest way to provide a supportable supply chain is through the employment of renewable biomass feedstocks, which is the only sustainable option to substitute for fossil fuel resources, as sources of organic compounds over a relatively short time scale and with limitless supply.